The Use of Interactive Learning Media for Teachers in Rural Areas - Anni Holila Pulungan (BIRCU, 2021)
Learning media is a tool or means that can facilitate delivery of messages from a learning resource to students. Interactive learning media need to be used by teachers so that the learning process runs well and is attractive to students. Teachers in rural areas still use conventional learning media. They still use simple media made of thick card and simple power point. There is no creation and innovation in it. The research method in this study is descriptive qualitative. Fifteen teachers from the Al Ahliyah Al Islamiyah madrasa, South Tapanuli. They are teachers who teach different subjects, such as Indonesian, Economics, Natural Sciences, Social Sciences, Chemistry, Information Communication Technology, and Mathematics as sources of research data. The purpose of this study was to explain the use of interactive learning media slide master by teachers in rural areas. Data collection techniques using observation, documentation and interviews. The validity of the data used triangulation techniques. Data analysis techniques using techniques of Miles and Huberman. The results obtained from this study indicate that teachers from various different subjects have used interactive learning media properly and correctly. This is based on the achievement of indicators on interactive learning media. And this has an impact on increasing students' learning achievement. And this has an impact on increasing students' learning achievement.